ADOPSI DALAM TIMBANGAN SYARIAT - Nadia Nadia; Nurinayah (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2021)
The aim of this research is to clarify adoption in Islamic law. In terms of history, adoption has been common until the beginning of the spread of Islam. The adoption practices or tabanni was then abolished by the revelation of instructions regarding adopted child through Surah al-Ahzab verses 4 and 5. These two verses remind of the prohibition of making adopted child like their biological child and then cutting off the lineage of the child. This practice then returned to become a culture for Muslims in Indonesia, due to the lack of literacy on this subject. Despite the many adoptions without a legal procedure, adoption based on Islamic law has applied formal juridical in the legal structure in Indonesia, the concept is different from tabanni which is closer to hadhanah in a broader sense in fiqh and is included in the category of child care in the Child Protection Laws.